Effects of Gamma-Tocotrienol on Partial-Body Irradiation-Induced Intestinal Injury in a Nonhuman Primate Model - Sarita Garg; Tarun K. Garg; Isabelle R. Miousse; Stephen Y. Wise; Oluseyi O. Fatanmi; Alena V. Savenka; Alexei G. Basnakian; Vijay K. Singh; Martin Hauer-Jensen (MDPI AG, 2022)
Exposure to high doses of radiation, accidental or therapeutic, often results in gastrointestinal (GI) injury. To date, there are no therapies available to mitigate GI injury after radiation exposure. Gamma-tocotrienol (GT3) is a promising radioprotector under investigation in nonhuman primates (NHP). We have shown that GT3 has radioprotective function in intestinal epithelial and crypt cells in NHPs exposed to 12 Gy total-body irradiation (TBI). Here, we determined GT3 potential in accelerating the GI recovery in partial-body irradiated (PBI) NHPs using X-rays, sparing 5% bone marrow. Sixteen rhesus macaques were treated with either vehicle or GT3 24 h prior to 12 Gy PBI. Structural injuries and crypt survival were examined in proximal jejunum on days 4 and 7. Plasma citrulline was assessed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Crypt cell proliferation and apoptotic cell death were evaluated using Ki-67 and TUNEL staining. PBI significantly decreased mucosal surface area and reduced villous height. Interestingly, GT3 increased crypt survival and enhanced stem cell proliferation at day 4; however, the effects seemed to be minimized by day 7. GT3 did not ameliorate a radiation-induced decrease in citrulline levels. These data suggest that X-rays induce severe intestinal injury post-PBI and that GT3 has minimal radioprotective effect in this novel model.